A Study of Farmers’ Awareness on Agricultural Insurance Schemes in Southern Haryana - M.S. Nain , Rashmi Singh and J.R. Mishra, (Indian Journal of Extension Education, 2017)
In the form of risk mitigating strategy insurance may play a vital role in anchoring a stable growth of agriculturalsector through reduction of the financial losses suffered by the farmers due to damage and destruction of theircrops, contents, machinery or accident with the farmer. The awareness regarding governmental initiatives hasalways been among the major hindering factors to take full advantage of the developmental efforts. The presentstudy conducted in two districts (Palwal and Faridabad) of southern Haryana (vulnerable to Earthquake, Industrial& Chemical Disaster, Floods, Drought, Accidents, Fire, Health related Disaster, Hailstorm, Bio Terrorism etc.) showsthat farmers awareness level regarding the agricultural insurance schemes was found at lowest ebb in terms of itscomponents and sub components. Number of constraints were reported by the respondent farmers hindering theacquisition of Agricultural Insurance Scheme which need immediate attention of the stakeholders to fulfill the loftydreams set forth in respect of the newly launched PradhanMantriFasalBimaYojna.